VIRAL HEPATITIS B IN PATIENTS WITH HEMATOLOGICAL MALIGNANCIES (ОVERVIEW) - V. N. Chebotkevich; S. S. Bessmeltsev; V. V. Danilchenko; E. I. Kajtandzhan; V. V. Burylev; E. E. Kiseleva; A. V. Chechetkin (Журнал инфектологии)
The review presents current data on the role of viral hepatitis B in on-cohematological patients. Possible ways of infection, prophylaxis of infection and activation of hepatitis B in this category of patients are considered. Specific features of the course of hepatitis B in various clinical situations are described: against the background of other viral infections and in the conduct of specific anti-leukemia therapy. The need to identify occult (occult) hepatitis in donors and patients with hemoblastosis is emphasized and methods for its detection are considered.